Survival, Retention, and Selective Proliferation of Lymphocytes Is Mediated by Gingival Fibroblasts - Moonen, Carolyn G. J.; Alders, Sven T.; Bontkes, Hetty J.; Schoenmaker, Ton; Nicu, Elena A.; Loos, Bruno G.; de Vries, Teun J. (Frontiers in Immunology, 2018)
Periodontitis, a chronic inflammatory disease of the periodontium, is characterized by osteoclast-mediated alveolar bone destruction. Gingival fibroblasts (GFs) present in the bone-lining mucosa, have the capacity to activate the formation of osteoclasts, but little is known about which local immune cells (co-)mediate this process. The aim of this study was to investigate the cellular interactions of GFs with immune cells, including the contribution of GFs to osteoclast formation and their possible role in the proliferation of these immune cells. In addition, we investigated the expression of adhesion molecules and the inflammatory cytokines that are evoked by this interaction. GFs were co-cultured with peripheral blood mononuclear cells (PBMCs), CD14+ monocytes or peripheral blood lymphocytes (PBLs) for 7, 14 and 21 days. After 21 days, comparable numbers of multinucleated cells (osteoclasts) were found in GF-PBMC and GF-monocyte co-cultures. No osteoclasts were formed in GF-PBL co-cultures, indicating that the PBLs present in GF-PBMC co-cultures do not contribute to osteoclastogenesis. Persisting mononuclear cells were interacting with osteoclasts in GF-PBMC co-cultures. Remarkably, a predominance of CD3+ T cells was immunohistochemically detected in GF co-cultures with PBLs and PBMCs for 21 days that frequently interacted with osteoclasts. Significantly more T, B (CD19+) and NK (CD56+CD3−) cells were identified with multicolor flow cytometry in both GF-PBMC and GF-PBL co-cultures compared to mono-cultures without GFs at all time points. GFs retained PBLs independently of the presence of monocytes or osteoclasts over time, showing a stable population of T, B and NK cells between 7 to 21 days. T helper and cytotoxic T cell subsets remained stable over time in GF co-cultures, while the number of Th17 cells fluctuated. Lymphocyte retention is likely mediated by lymphocyte-function-associated antigen-1 (LFA-1) expression, which was significantly higher in GF-PBL cultures compared to GF-monocyte cultures. When assessing inflammatory cytokine expression, high TNF-α expression was only observed in the GF-PBMC cultures, indicating that this tripartite presence of GFs, monocytes, and lymphocytes is required for such an induction. CFSE-labeling showed that only the CD3+ cells proliferated in presence of GFs. This study demonstrates a novel role for GFs in survival, retention, and selective proliferation of lymphocytes.